(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the changes in regional lung ventilation distribution, as measured by Electrical Impedance Tomography (EIT), and its associated factors in patients with Acute Respiratory Distress Syndrome (ARDS) undergoing prone ventilation. Subjects and Methods: This descriptive study included a total of 24 patients with severe ARDS who received prone mechanical ventilation and EIT monitoring at the Center for Critical Care Medicine, Bach Mai Hospital, from May 2024 to September 2025. EIT measurements of posterior tidal ventilation (TVP), ventilation in the most dependent lung region (TVROI4), and the anterior-to-posterior ventilation ratio (A/P) were recorded at predefined time points. Data were analyzed using SPSS software. Results: The study was conducted on 24 patients with ARDS (62.5% male) with a mean age of 55.1 ± 21.3 years. The mean SOFA score was 11.42 ± 3.02, mean APACHE II score was 21.25 ± 5.51, and mean LIS was 2.83 ± 0.37. Patients had severe ARDS with an initial mean PaO₂/FiO₂ ratio of only 97.97 ± 25.32 and a very low mean static compliance (Cstat) of 22.76 ± 8.19 mL/cmH₂O. At baseline, EIT showed heterogeneous ventilation distribution, predominating in the anterior regions (TVA 56%) compared to the posterior regions (TVP 44%), with a mean A/P ratio of 1.49. After 16 hours of prone positioning, ventilation was significantly redistributed, with TVP increased from 44% to 47.5% (p < 0.05) and the A/P ratio decreased from 1.49 to 1.04 (p < 0.05), indicating improved homogeneity of ventilation, while the Right/Left distribution remained stable. 17 out of 24 patients (70.8%) responded to prone ventilation. Those with initially heterogeneous ventilation distribution (A/P > 1 or reduced ventilation in the dorsal regions) had a higher response rate (87.5%). Conclusion: In patients with severe ARDS undergoing prone ventilation, EIT demonstrated an initially heterogeneous ventilation distribution that improved over time with prone positioning. Ventilation distribution patterns assessed by EIT were associated with changes in oxygenation following prone ventilation; however, further studies with control groups and more robust study designs are required to evaluate the prognostic value of EIT.